If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 3(-2) = 0 Multiply 3 * -2 5 + -6 = 0 Combine like terms: 5 + -6 = -1 -1 = 0 Solving -1 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| log[2](3x+3)=2 | | 3y^2+x+18y+27=0 | | -23=-x/2 | | -x/8=46 | | 5-6m=3 | | 2x^3+7x^2+4x-3=0 | | x^4=.0016 | | 6-5h=-34 | | 12(6c-1)-18=70c+12 | | 2/5w-6=7/5 | | x+21=2x+9 | | 16p^2=25 | | 1/5(2x-2)=8 | | -8(11y)= | | 10x^2+3X+15=0 | | f(x)=2x-6 | | 0=-6x^2+2x+4 | | 0=-6x^2+5x+7 | | 3(2z-2)-3(4-5z)=6 | | 1/2(4-6x) | | 3(n-1)-2=4(n+2)+4 | | 5b-3(4-b)=3(b+21) | | 29+4(2n-11)=1 | | 12+6(z-2)=-2z+5 | | log(8)(2-5x)=log(8)(-4x+3) | | 6-3(2x-4)=1(1+x) | | 6-3(2x-4)=2(1-x) | | 6z+8-1/2(2z-20)=18 | | y-16-3(-8)=0 | | c^2-8c+16=4 | | 6a-3=4-7a | | y^2-15y-16=0 |